2016
DOI: 10.1186/s13017-016-0094-1
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Assessment as a qualification element for elective and emergency cholecystectomy in older patients

Abstract: BackgroundOlder patients experience a higher incidence of postoperative complications after cholecystectomy compared with younger patients. However, most studies have not considered patient frailty, particularly regarding emergency cholecystectomy. The aim of this prospective study was to evaluate outcomes in frail older patients eligible for elective and emergency cholecystectomy.MethodsPreoperative Geriatric Assessment (GA) was performed in consecutive patients aged 65+ years, operated for biliary disease. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Many surgeons hesitate to operate on older patients with symptomatic cholelithiasis. However, we have shown in our previous study that elective laparoscopic cholecystectomy, in experienced hands, is safe, even in frail older patients, and can be performed with minor morbidity and no mortality [19].…”
Section: Discussionmentioning
confidence: 88%
“…Many surgeons hesitate to operate on older patients with symptomatic cholelithiasis. However, we have shown in our previous study that elective laparoscopic cholecystectomy, in experienced hands, is safe, even in frail older patients, and can be performed with minor morbidity and no mortality [19].…”
Section: Discussionmentioning
confidence: 88%
“…Secondly, chronological age has many limitations and data on biological fitness is lacking to explain why elderly patients develop poorer outcomes compared to younger patients [32]. For example, prospective scoring of patient frailty, an increasingly recognised feature associated with poor postoperative outcomes, is lacking [7,33]. Thirdly, a precise scoring of intraoperative cholecystectomy difficulty is lacking [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]14,15 Despite these results, and in accordance with the present study, large series of elderly patients submitted to cholecystectomy have been published with favorable results in terms of morbidity and mortality (ranging from 0.2% to 22%) 3, [14][15][16] demonstrating that preoperative morbidity factors played a much more relevant role in terms of survival than age itself. 11,16,17 The circumstances of surgery are relevant, as demonstrated by Nielsen et al and others, with a reported 63% of uneventful postoperative course when cholecystectomy was performed electively. 3,11,18 Moreover, urgent surgery was identified in the current study, as a poor prognostic factor for octogenarians undergoing cholecystectomy.…”
Section: Discussionmentioning
confidence: 98%